CASE AR AND VR. EVOLUTION OF AUGMENTED REALITY - Uatbaev, J.J.; Zharlykasov, B.J. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2020)
This article is about augmented and virtual reality, the first possible implementations of them. The article begins with a brief description of virtual and augmented reality technologies. The history of the development of these technologies is described below.
Keywords: Аugmented reality; AR; VR; smartphone; glasse